Esophageal Intramural Pseudodiverticulosis and Concomitant Eosinophilic Esophagitis: A Case Series - Michael A. Scaffidi; Ankit Garg; Brandon Ro; Christopher Wang; Tony T. C. Yang; Ian S. Plener; Andrea Grin; Errol Colak; Samir C. Grover (Canadian Journal of Gastroenterology and Hepatology)
Background. Esophageal intramural pseudodiverticulosis (EIPD) is an idiopathic benign chronic disease characterized by flask-like outpouchings of the esophageal wall. It is unknown whether there is a genuine association between EIPD and eosinophilic esophagitis (EoE). Aims. To investigate a possible relationship between EIPD and EoE. Methods. Patients with radiographic or endoscopic evidence of pseudodiverticulosis were identified from the database at a single academic center. Cases were analyzed in three areas: clinical information, endoscopic findings, and course. Results. Sixteen cases of esophageal pseudodiverticulosis were identified. Five patients had histologic evidence of eosinophilic esophagitis. Patients with EoE had pseudodiverticula in the mid-to-distal esophagus while those with EIPD had pseudodiverticula predominantly in the proximal esophagus (p<0.001). EoE with pseudodiverticulosis occurred in younger patients (p<0.019). Food bolus obstructions were more common in patients with EoE and pseudodiverticulosis than in EIPD (p<0.034). Conclusions. This is the first case series supporting a potential association between EoE and pseudodiverticulosis. We also identify characteristic features of pseudodiverticulosis that may raise clinical suspicion of underlying eosinophilic esophagitis.